In-situ carbon-doped modified lithium iron silicate and preparation method thereof
Patent Information
- Application Number
- CN202511502648.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-21
AI Technical Summary
[0004]本发明第一目的是提供一种原位碳掺杂改性硅酸亚铁锂制备方法,解决现有技术中碳改性硅酸亚铁锂的碳包覆层易开裂,厚度不均匀的不足
[0026](1)本发明原位碳掺杂改性硅酸亚铁锂材料的制备方法,通过制备酚醛树脂/二氧化硅复合中空球前驱体,前驱体中形成了较为稳定的Si-C键,再以此为硅源制备出原位碳掺杂改性的硅酸亚铁锂材料,与杂原子掺杂碳层改性相比,本发明的原位碳掺杂改性方法,可以减少副反应的发生,避免碳层的破裂,改性更加均匀,制备工艺简单,成本较低。
Smart Images

Figure CN121377054B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to an in-situ carbon-doped modified lithium iron silicate, and also to a method for preparing the in-situ carbon-doped modified lithium iron silicate. Background Technology
[0002] The rapid depletion of traditional fossil fuels and increasingly serious environmental problems are driving the continuous pursuit of new energy storage systems. Further development of high-performance energy storage devices is also necessary for the development of emerging industries such as electric vehicles and portable electronic devices. Among energy storage devices, rechargeable lithium-ion batteries (LIBs) have become the core energy carrier in the fields of power batteries and grid energy storage due to their advantages such as high energy density, high reliability, and high efficiency. With the acceleration of industrialization, developing high-performance, low-cost cathode materials has become a key challenge in improving the overall performance of lithium-ion batteries. Currently, the polyanionic cathode material Li2FeSiO4 (LFS) boasts a high theoretical capacity (332 mAh g / g). -1 Li has attracted widespread attention due to its high thermal stability and low cost. However, its low electronic conductivity and low thermal stability have also contributed to its development. + The slow diffusion and other drawbacks of lithium ions limit their practical application in electrochemical performance. Therefore, extensive research has been conducted, including reducing particle size to the nanoscale, coating with carbon or other conductive materials, doping with metal ions, and morphology manipulation. Among these, carbon material modification has been shown to create high-speed electron channels, improving conductivity and shortening the lithium-ion diffusion path, making it an effective way to enhance the electrochemical performance of materials. Currently, there are three main methods for modifying carbon materials: carbon coating, multi-level carbon structures, and heteroatom-doped carbon layers. Carbon coating involves first synthesizing a Li₂FeSiO₄ precursor using a sol-gel or solid-state method, then incorporating carbon sources such as sucrose, glucose, or polyvinyl alcohol, followed by secondary sintering (600–750℃) under an inert atmosphere to obtain a 5–20 wt% carbon coating layer. The construction of hierarchical carbon structures utilizes reduced graphene oxide (rGO) or carbon nanotubes to build a three-dimensional conductive network, accelerating electron transport. Heteroatom-doped carbon layers, such as nitrogen doping, primarily use tartaric acid as the carbon source and urea as the nitrogen source, followed by nitriding at 700℃ after sol-gel to obtain an NC layer (N content -3 at%), reducing charge transfer impedance. These methods can improve the material's shortcomings to some extent, but they also have some problems. For example, when the carbon content in the carbon coating is low, the improvement in conductivity is limited; when it is high, it reduces tap density and energy density. The construction process for hierarchical carbon structures is long and costly. Heteroatom-doped carbon layers may trigger side reactions, generating impurity phases that significantly affect the electrochemical performance of the material.
[0003] Therefore, this invention proposes a method for preparing in-situ carbon-doped modified lithium iron silicate material. A phenolic resin / silica composite hollow sphere precursor is prepared, an iron source and a lithium source are added, and a modified lithium iron silicate precursor is obtained by hydrothermal synthesis. After calcination, the in-situ carbon-doped modified lithium iron silicate material is finally prepared. The preparation process is simple and the cost is low. Summary of the Invention
[0004] The primary objective of this invention is to provide an in-situ carbon-doped modified lithium iron silicate preparation method, which addresses the shortcomings of existing technologies where the carbon coating layer of carbon-modified lithium iron silicate is prone to cracking and has uneven thickness.
[0005] The second objective of this invention is to provide an in-situ carbon-doped modified lithium iron silicate.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0008] S1. Phenolic resin / silica composite hollow spheres were prepared using resorcinol, formaldehyde and silicon source, and then iron source and lithium source were added to react. Modified lithium iron silicate precursor was then synthesized by hydrothermal method.
[0009] S2. The modified lithium iron phosphate precursor obtained in S1 is calcined in an inert gas atmosphere to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0010] The present invention discloses an in-situ carbon-doped modified lithium iron silicate preparation method. First, phenolic resin / silica composite hollow spheres are prepared. Using these as reactants and templates, iron and lithium sources are added, and modified lithium iron silicate precursors are synthesized by hydrothermal method. During the calcination process, phenolic resin acts as a carbon precursor. The reducing gas such as carbon monoxide generated during the carbonization process reduces ferric iron to ferrous iron, and finally, in-situ carbon-doped modified lithium iron silicate material is synthesized.
[0011] In this invention, S1 uses resorcinol, formaldehyde, and a silicon source to prepare phenolic resin / silica composite hollow spheres. The specific process is as follows: a block polyurethane surfactant is dispersed in water, an oil phase is added, the pH is adjusted to 5-8, resorcinol and formaldehyde are added and stirred, and a silicon source is added to react, thereby obtaining phenolic resin / silica composite hollow spheres.
[0012] Furthermore, the oil phase is one or more of P123, cyclohexane, paraffin, petroleum ether, stearic acid, and octadecyl alcohol.
[0013] Furthermore, the pH is 5-6.
[0014] In this invention, the mass ratio of the block polyurethane surfactant, the oil phase, and water is 1:1 to 4:20.
[0015] In this invention, the ratio of resorcinol, formaldehyde and silicon source added is 0.25g-0.35g: 0.4ml-0.5ml: 0.8ml-1.2ml.
[0016] In this invention, the molar ratio of Li, Fe, and Si elements in the lithium source, iron source, and silicon source is 1.5-2:0.6-1.0:0.6-1.0.
[0017] In this invention, the silicon source is one or more of tetraethyl orthosilicate, aminopropyltriethoxysilane, vinyltrimethoxysilane, and trimethoxyphenylsilane.
[0018] In this invention, the block polyurethane surfactant is prepared by the following method: isocyanate is heated to 70°C to 90°C, then an organotin catalyst is added, followed by the addition of 2,2-dimethylolpropionic acid and reacted for 1 to 3 hours. The reaction product is then added to polyethylene glycol preheated to 60°C to 100°C and reacted for 1 to 3 hours. Finally, volatile components are removed by vacuum to obtain the block polyurethane surfactant.
[0019] Furthermore, the molar ratio of the isocyanate, 2,2-dimethylolpropionic acid, and polyethylene glycol is 1:0.5-0.8:0.03-0.08.
[0020] In this invention, the iron source is one or more of ferric nitrate, ferric oxalate, ferric citrate, and ferric chloride.
[0021] In this invention, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium chloride, and lithium nitrate.
[0022] In this invention, the inert gas is one of argon, nitrogen, and carbon dioxide.
[0023] In this invention, the calcination temperature in S2 is 600℃-700℃, and the calcination time is 9h-11h.
[0024] An in-situ carbon-doped modified lithium iron silicate was prepared by the above method.
[0025] The present invention has the following beneficial effects:
[0026] (1) The preparation method of the in-situ carbon-doped modified lithium iron silicate material of the present invention involves preparing a phenolic resin / silica composite hollow sphere precursor, in which relatively stable Si-C bonds are formed. The precursor is then used as a silicon source to prepare the in-situ carbon-doped modified lithium iron silicate material. Compared with the heteroatom doped carbon layer modification, the in-situ carbon doping modification method of the present invention can reduce the occurrence of side reactions, avoid the cracking of the carbon layer, and achieve more uniform modification. The preparation process is simple and the cost is low.
[0027] (2) The method of the present invention prepares in-situ carbon-doped modified lithium iron silicate material for use as a lithium-ion battery electrode material, which has good rate performance and high reversible capacity, and also has good cycle performance. Attached Figure Description
[0028] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0029] Figure 1 This is a SEM image of silicon-carbon precursor composite hollow spheres;
[0030] Figure 2 These are XRD patterns of lithium iron silicate materials modified with different carbon-silicon ratios in Examples 1-3;
[0031] Figure 3 These are rate performance graphs of lithium iron silicate materials modified with different carbon-silicon ratios in Examples 1-3;
[0032] Figure 4 These are cycle stability graphs of lithium iron silicate materials modified with different carbon-silicon ratios in Examples 1-3;
[0033] Figure 5 These are the EIS diagrams of lithium iron silicate materials modified with different carbon-silicon ratios in Examples 1-3;
[0034] Figure 6 The low-frequency regions Z' and ω of lithium iron silicate materials modified with different carbon-silicon ratios in Examples 1-3 are... -1 / 2 picture. Detailed Implementation
[0035] This invention proposes a method for preparing in-situ carbon-doped modified lithium iron phosphate (LiFeSO4) materials, overcoming the shortcomings of other carbon material modification methods, such as uneven coating, easy generation of impurity phases, and poor modification effect. Using a hollow composite material as a precursor, the hollow structure provides elastic space for volume expansion during charging and discharging, buffering the stress generated by volume expansion. Furthermore, the porous or thin-shell characteristics of the hollow structure shorten the lithium-ion diffusion path, while the cavity and shell surface form a continuous ion / electron transport network, which is beneficial for improving lithium-ion diffusion. The method uses a block polyurethane surfactant as a template agent to prepare a phenolic resin / silica composite hollow sphere precursor. Iron and lithium sources are added, and the modified LiFeSO4 precursor is synthesized using a hydrothermal method. During calcination, the phenolic resin acts as a carbon precursor, and the reducing gas, such as carbon monoxide, generated during carbonization reduces ferric iron to ferrous iron, ultimately synthesizing the in-situ carbon-doped modified LiFeSO4 material.
[0036] In the following examples, the block polyurethane surfactant was prepared by the following method: isocyanate was heated to 70°C–90°C, then an organotin catalyst was added, followed by the addition of 2,2-dimethylolpropionic acid, and the reaction was carried out for 1–3 hours. The reaction product was then added to polyethylene glycol preheated to 60°C–100°C and reacted for 1–3 hours. Volatile components were then removed under vacuum to obtain the block polyurethane surfactant. The molar ratio of isocyanate, 2,2-dimethylolpropionic acid, and polyethylene glycol was 1:0.5–0.8:0.03–0.08.
[0037] Example 1
[0038] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0039] (1) Take 1g of block polyurethane surfactant and stir to disperse in 20g of water; adjust the pH of the solution to 5-7, add 4g of cyclohexane and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1.2ml of aminopropyltriethoxysilane and react for 24 hours.
[0040] 1.89 g of ferric nitrate nonahydrate and 1.19 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180°C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0041] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0042] Example 2
[0043] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0044] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7, add 4g of cyclohexane and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0045] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0046] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0047] Example 3
[0048] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0049] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7, add 4g of cyclohexane and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 0.8ml of aminopropyltriethoxysilane and react for 24 hours.
[0050] 2.646 g of ferric nitrate nonahydrate and 1.67 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180°C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0051] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0052] Example 4
[0053] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0054] (1) Take 1g of block polyurethane surfactant and stir to disperse in 20g of water; adjust the pH of the solution to 5-7, add 2g of cyclohexane and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0055] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0056] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0057] Example 5
[0058] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0059] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7, add 3g of cyclohexane and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0060] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0061] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0062] Example 6
[0063] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0064] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7, add 4g of paraffin and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0065] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0066] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0067] Example 7
[0068] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0069] (1) Take 1g of block polyurethane surfactant and stir to disperse in 20g of water; adjust the pH of the solution to 5-7, add 4g of petroleum ether and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0070] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0071] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0072] Example 8
[0073] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0074] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7, add 4g of P123 and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane and react for 24 hours.
[0075] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0076] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0077] Comparative Example 1
[0078] A method for preparing in-situ carbon-doped modified lithium iron silicate includes the following steps:
[0079] (1) Take 1g of block polyurethane surfactant and stir to disperse it in 20g of water; adjust the pH of the solution to 5-7 and stir for 30min; add 0.3g of resorcinol and 0.42ml of formaldehyde to the above solution, stir for 30min and then add 1ml of aminopropyltriethoxysilane to react for 24 hours.
[0080] 2.27 g of ferric nitrate nonahydrate and 1.43 g of lithium acetate dihydrate were added sequentially to the above solution, and the reaction was allowed to proceed for 24 hours. After the reaction was complete, the solution was transferred to a hydrothermal reactor and placed in an oven at 180 °C for 24 hours. The modified lithium iron phosphate precursor was then obtained by centrifugation and washing.
[0081] (2) The modified lithium iron phosphate precursor was placed in a tube furnace and heated to 650°C at 5°C / min in a nitrogen atmosphere and held for 10 hours to obtain in-situ carbon-doped modified lithium iron phosphate material.
[0082] I. Electrochemical Performance Testing of In-situ Carbon-Doped Modified Lithium Iron Silicate Materials
[0083] Electrochemical performance tests were conducted on the in-situ carbon-doped modified lithium iron phosphate materials prepared in Examples 1-8 and Comparative Example 1. The electrochemical performance tests used a half-cell, with a lithium metal sheet as the counter electrode, Celgard 2500 as the separator, and a 1.0 mol / L LiPF6 mixture of ethylene carbonate, diethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate, wherein the volume ratio of ethylene carbonate to diethyl carbonate was 1:1:1, the fluoroethylene carbonate content was 5%, polyvinylidene fluoride was used as the binder, and Ketjen Black was used as the conductive agent. The positive electrode material Li2FeSiO4: Ketjen Black:PVDF was ground and mixed in a ratio of 8:1:1. PVDF was dissolved in NMP, and the mixture was stirred, prepared, film-formed, pressed, punched, vacuum-dried, and weighed to prepare the positive electrode sheet. A coin-type CR2032 half-cell was assembled in a glove box, and after resting, the voltage range for testing was set to 1.5V–4.8V. The results are shown in Table 1.
[0084] Table 1. Electrochemical performance of in-situ carbon-doped modified lithium iron silicate materials prepared in different embodiments and comparative examples.
[0085]
[0086] The effects of different carbon-silicon ratios and different oil phase contents and types on the electrochemical performance of the in-situ carbon-doped modified lithium iron silicate material prepared in this invention were investigated through Examples 1-8 and Comparative Example 1. Among them, Example 2 showed the best electrochemical performance, with a first-cycle charge specific capacity of 175.32 mAh / g, a first-cycle discharge specific capacity of 172.85 mAh / g, and a coulombic efficiency of 98.60%.
[0087] II. Effect of Carbon-to-Silicon Ratio on Electrochemical Performance of In-situ Carbon-Doped Modified Lithium Iron Silicate Materials
[0088] To further investigate the effect of the carbon-silicon ratio, further characterization and electrochemical performance tests were conducted on Examples 1-3 (carbon-silicon ratios of 3:1, 3.5:1, and 4:1, respectively). The results are as follows:
[0089] (1) SEM image ( Figure 1 The results show that the phenolic resin / silica composite hollow sphere precursor exhibits a microstructure of an airless balloon.
[0090] (2) XRD diagram Figure 2 The XRD pattern of Example 2 shows no impurity phases, indicating a relatively pure phase. However, the XRD patterns of Examples 1 and 3 show impurity peaks for Li₂SiO₃ and Fe, indicating impure synthesized products. This demonstrates that the carbon-to-silicon ratio has a significant impact on the lithium iron silicate material of this invention; a suitable carbon-to-silicon ratio can reduce the formation of impurity phases. A higher carbon-to-silicon ratio may lead to Fe... 3+ Excessive reduction to elemental iron leads to defects in the crystal structure and a decrease in specific capacity. A lower carbon-to-silicon ratio may result in the formation of partial Fe. 3+ Not reduced to Fe 2+ The unreacted silicon and lithium resulted in the formation of Li2SiO3 impurities due to excess silicon and lithium.
[0091] (3) Rate performance diagrams of lithium iron phosphate materials modified with different carbon-silicon ratios ( Figure 3 As shown, Example 2 exhibits the best rate performance and high reversible capacity.
[0092] (4) Cyclic stability diagrams of lithium iron silicate materials modified with different carbon-silicon ratios ( Figure 4 The results show that Example 2 exhibits the best cycling performance, with a capacity retention of 93.1% after 100 cycles.
[0093] III. Lithium-ion kinetics performance testing of in-situ carbon-doped modified lithium iron silicate materials
[0094] The lithium-ion kinetics performance of the in-situ carbon-doped modified lithium iron silicate materials prepared in Examples 1-3 was tested. Electrochemical impedance spectroscopy (EIS) was performed using a CHI660E electrochemical workstation manufactured by Shanghai Chenhua Instrument Co., Ltd., with a frequency range of 0.01Hz-100kHz and an amplitude of 5mV. The test results were fitted and analyzed using Zview software. The results are as follows:
[0095] (1) Electro-acoustic impedance (EIS) test diagram ( Figure 5 The equivalent circuit consists of Warburg impedance (Zw), charge transfer impedance (Rct), phase constant element (CPE), and electrolyte impedance (Re). The charge transfer resistances calculated according to the formula are summarized in Table 2. Example 2 has the lowest charge transfer resistance of 84.58 Ω, indicating better lithium-ion kinetic performance.
[0096] Table 2. AC impedance test results of in-situ carbon-doped modified lithium iron phosphate materials prepared in Examples 1-3.
[0097]
[0098] (2) Low-frequency region Z' and ω -1 / 2 Relationship diagram ( Figure 6 The data shows that the slope in the low-frequency region represents the Warburg impedance (Zw), which is related to the diffusion rate of lithium ions in the electrode material. A larger slope indicates a higher Li-ion diffusion rate. + The slower the diffusion rate and the smaller the slope, the better the Li + The faster the diffusion rate, the better. According to the fitting results, the curve slope of Example 2 is the smallest at 48.44.
[0099] The above embodiments of the present invention are not intended to limit the scope of protection of the present invention. The implementation of the present invention is not limited thereto. All other modifications, substitutions or alterations made to the above structure of the present invention based on the above content of the present invention, in accordance with ordinary technical knowledge and common practice in the field, without departing from the basic technical idea of the present invention, shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing in-situ carbon-doped modified lithium iron silicate, characterized in that, Includes the following steps: S1. Phenolic resin / silica composite hollow spheres were prepared using resorcinol, formaldehyde and silicon source, and then iron source and lithium source were added to react. Modified lithium iron silicate precursor was then synthesized by hydrothermal method. S2. The modified lithium iron phosphate precursor obtained in S1 is calcined in an inert gas atmosphere to obtain in-situ carbon-doped modified lithium iron phosphate material. In S1, phenolic resin / silica composite hollow spheres are prepared using resorcinol, formaldehyde, and a silicon source. The specific process is as follows: a block polyurethane surfactant is dispersed in water, an oil phase is added, the pH is adjusted to 5-8, resorcinol and formaldehyde are added and stirred, and a silicon source is added to react, thereby obtaining phenolic resin / silica composite hollow spheres; the mass ratio of the block polyurethane surfactant, oil phase, and water is 1:1-4:20; the addition ratio of resorcinol, formaldehyde, and silicon source is 0.25g-0.35g:0.4ml-0.5ml:0.8ml-1.2ml.
2. The method for preparing in-situ carbon-doped modified lithium iron silicate according to claim 1, characterized in that, The oil phase is one or more of P123, cyclohexane, paraffin, petroleum ether, stearic acid, and octadecyl alcohol.
3. The method for preparing in-situ carbon-doped modified lithium iron silicate according to claim 1, characterized in that, The silicon source is one or more of tetraethyl orthosilicate, aminopropyltriethoxysilane, vinyltrimethoxysilane, and trimethoxyphenylsilane.
4. The method for preparing in-situ carbon-doped modified lithium iron silicate according to claim 1, characterized in that, The molar ratio of Li, Fe, and Si elements in the lithium source, iron source, and silicon source is 1.5-2:0.6-1.0:0.6-1.
0.
5. The method for preparing in-situ carbon-doped modified lithium iron silicate according to any one of claims 1-4, characterized in that, The block polyurethane surfactant is prepared by the following method: isocyanate is heated to 70℃~90℃, then an organotin catalyst is added, followed by the addition of 2,2-dimethylolpropionic acid and reacted for 1h~3h. The reaction product is then added to polyethylene glycol preheated to 60℃~100℃ and reacted for 1h~3h. The volatile components are then removed by vacuum to obtain the block polyurethane surfactant.
6. The method for preparing in-situ carbon-doped modified lithium iron silicate according to claim 5, characterized in that, The iron source is one or more of ferric nitrate, ferric oxalate, ferric citrate, and ferric chloride; the lithium source is one or more of lithium carbonate, lithium nitrate, lithium acetate, and lithium chloride.
7. The method for preparing in-situ carbon-doped modified lithium iron silicate according to claim 5, characterized in that, The calcination temperature of S2 is 600℃-700℃, and the calcination time is 9h-11h.
8. An in-situ carbon-doped modified lithium iron silicate, characterized in that, It is prepared by the method described in any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of carbon nano-Li2FeSiO4 composite cathode material
CN102709561A
Metallic member with antirust coating layer
JP2004322573A